The possibilites of international prosecution against the former Somali militry regime for human rights abuses in Somaliland from 1981 - 1991: establishing individual criminal and civil responsibility under international law - Viljoen, Frans (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2008.